The Effectiveness of Kahoot Online Media in Learning Personal Pronoun at a State Senior High School in Jambi City - Suyadi Suyadi; Bujing Bujing; Husnaini Husnaini (State Islamic University of Raden Fatah Palembang, South Sumatra, Indonesia, 2020)
This study is aimed at finding the effectiveness of Kahoot online media in learning personal pronoun for senior high school students. There were 30 social sciences students taken as participants in control class, and 30 natural sciences students were taken as experimental participants. There were five (5) topics given to the students; objective, subjective, possessive pronoun, possessive adjective, and reflexive as mains materials in English subject. The results of the research were proven effective by using t-test. Students’ scores in learning personal pronoun were significant after implementing Kahoot online media. The average pre-test control class 37,1 and post-test control class 48,7. Average pre-test experimental class 41,5 and post-test experimental class 83,5. Kahoot online media makes learning process more interesting. The value of t-test higher than the value of t-table (26,11> 2,001).